Aspergillus Niger 129B promotes plant growth by inducing the interaction between SAUR32 and PP2C72 - He, Juan; Gao, Li Yuan; Luo, Yong Ping; Chai, Min; Wang, Hua Feng; Yang, Lu Hong; Zhao, Kang; Maimaiti, Yushanjiang; Nie, Yuan Jun; Chen, Wei (Frontiers in Microbiology, 2025)
IntroductionPlant growth-promoting fungi (PGPF) play a fundamental role in plant development, such as nutrient acquisition and root growth. However, the growth promotion mechanisms regulated by Aspergillus niger are poorly characterized.MethodsWe examined the growth-promoting effects of Aspergillus niger 129B on tomato plant root, stem, and leaf development through a combination of phenotype analyses and plant biomass measurement. Subsequently, molecular and genetic experiments were conducted to reveal the mechanism promoting root, stem, and leaf development.ResultsIt demonstrated that 129B significantly promoted the growth of tomato plants. Plant transcriptome and metabolome analysis revealed that this effect was associated with the plant hormone signaling pathway, particularly the expression of SAUR32 and PP2C72 genes. In addition, 129B could promote the development of root, stem, and leaf tissues by downregulating the expression of SAUR32 and PP2C72 genes. Importantly, we found that the promotion of tissue development may be attributed to the interaction between SAUR32 and PP2C72; the expression of SAUR32 proteins, which act as inhibitors of PP2C72 phosphatases, triggered root H+ efflux.DiscussionOur findings concluded that 129B-induced plant promotion is dependent on the interaction between SAUR32 and PP2C72, providing novel insights into beneficial plant–microbiome interactions.